EVALUASI PENGGUNAAN FORMULIR PAISEN RAWAT JALAN DI RSUP DR. SARDJITO YOGYAKARTA - , BUDI KURNIANINGSIH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: medical record Form serves as a data collection tool that is associated with the patient in the hospital. Medical record forms need to be clearly designed, neat, interesting and informative in order to facilitate users in understanding and fill out the form so that the incomplete medical record form pengisan can be minimised.The medical record form must be evaluated in order to comply with what is required by the parties concerned Purpose: To evaluate design form viewed from three (3) components of a physical component, namely anatomic components, the component contents. Form subjects such as a form of the old and form the polyclinic the eye used currently. Research methods: this type of research is descriptive research design qualitative case studies. Data retrieval through observation, interview and documentation study, namely, an interview with the doctor as A respondent, the staff medical record as the respondent B, a nurse at the clinic as a respondent C as a medical record staff and Chief of outpatient installation as a triangulation of sources. Research results: physical components that are in accordance with the type of HVS kuarto paper (A4) size 21.6 x 28 cm and paper weight 80 grams. Judging from the anatomical component that is part of the description (instruction) and content (body) has not been in accordance with the rules and the existing theory. On the component content determination of items which should be listed do not meet due to a doubling of the item as well as a sense of the items less detail so as to make users confused as to fill out the form. So the presence of the addition and subtraction of existing items in the form outpatient eye clinic in use today so that the information obtained is informative. Note on the component development known as SOAP, the component is in compliance with the order of examination of S, namely subjective note in accordance with the statement of the patient and symptoms. O namely noted load findings in objective, such findings are the result of laboratory test results, and observations of the physical examination. Letter A analysis (assessment service) which is reviewing and assessing the findings and observations. The letter P as planning (plan) should describe the records about the next service plan and revise services that have been provided.